Impact of creative workshops for people with severe mental illness: art as a means of recovery - Saavedra, Javier; Arias, S.; Crawford, Paul; Perez, Elvira (Taylor and Francis, 2017)
Background: In line with recovery theories, psychosocial programs for people diagnosed with severe mental illness (SMI) should focus more on wellbeing and social connectivity outcomes rather than clinical symptoms. This paper assesses the impact of creative workshops participation on the psychological wellbeing, social connectivity and subjective experience of people diagnosed with SMI. Method: After participating in a creative workshop in a museum, 19 people, including service users, keyworkers, the art facilitator and a psychologist were interviewed. Four observers participated in the workshop and provided information about the creative process by means of a discussion group. Data was analysed in accordance with thematic analysis methodology and triangulated in order to obtain reliability. Results: Five essential categories were identified: learning process, social connection, psychological wellbeing, institutional change and mutual recovery. Conclusions: Creative activities may cause a transformation of the image of dysfunction associated with mental illness as well as promoting health and recovery.